Sentana Paperasan's Legal Efforts as a Solution to Overcoming Decisions in Banjar Kutuh, Sayan Village, Ubud District, Gianyar Regency - MAHENDRA, I Komang Arya Sentana; WESNA, Putu Ayu Sriasih; UTAMA, I Wayan Kartika Jaya (Protection: Journal Of Land And Environmental Law, 2023)
The process of adopting children is not only regulated based on national law, but also regulated according to customary law or often referred to as awig-awig which exists in each traditional village in Bali. In this study, empirical legal research methods will be used which will focus on the discrepancies that occur in accordance with the theory of the reality that occurs in society. The discussion that will be described in this study includes the position and legal protection of sentana extortion in inheritance at Banjar Kutuh, Sayan Village, Ubud District, Gianyar Regency. The position of the custodian of inheritance in Banjar Kutuh, Sayan Village, Ubud District, Gianyar Regency in overcoming the decision, namely in Balinese Customary Law, a child who has undergone the process of extortion ceremony is bound by his family relationship with the adoptive parent accompanied by severance of the relationship with his biological family. Where the relationship of a sentana (adopted child) with his biological parents is erased when they have undergone an extortion ceremony procession. Legal Protection Against Sentana Extortion in Inheritance under Article 832 jo.842 jo. Article 852 (a) of the Civil Code, based on an analysis using the theory of justice and the theory of legal protection, adopted children are included as heirs who inherit based on their own position in the First class in obtaining inheritance rights from their adoptive parents, thereby closing the rights of other heirs.